The Intricacies of Attracting and Sustaining Investment in WASH in Fragile States : Lessons from Liberia - de Waal, Dominick; Hirn, Max (World Bank, Nairobi, Kenya, 2016)
The choice made early in the post-conflict transition by the international community to directly fund WASH service delivery through non-state actors rather than through the Liberian government undermined both sector policy dialogue and the formation of robust government institutions able to lead and orchestrate service delivery by non-state actors. This paper aims to inform this new wave of support to Liberia’s WASH sector by looking back at service provision in the country over the period 2003 to 2015 and reflecting on the transition from the post-war emergency response to the nascent development response. The paper first describes key trade-offs encountered by the international community in this transition, describing choices made in Liberia that held back government capacity to orchestrate a national response to service delivery. It then goes on to describe how WSP and other development partners have, since 2011, worked with the government of Liberia to build and attract investment to a country-led WASH development program. The paper presents lessons for sector practitioners operating in post-crisis transition situations, both those in developing country governments and their development partners.